2021
DOI: 10.1186/s12870-021-02911-z
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome behavior during meiosis in pollen mother cells from Saccharum officinarum × Erianthus arundinaceus F1 hybrids

Abstract: Background In recent years, sugarcane has attracted increasing attention as an energy crop. Wild resources are widely used to improve the narrow genetic base of sugarcane. However, the infertility of F1 hybrids between Saccharum officinarum (S. officinarum) and Erianthus arundinaceus (E. arundinaceus) has hindered sugarcane breeding efforts. To discover the cause of this infertility, we studied the hybridization process from a cytological perspective. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Micronucleus formation was caused by chromosome lag that prevented chromosomes from entering newly formed cells [27] . The formation of lagging chromosomes is a product of several pre-anaphasic chromosomal irregularities [28] .…”
Section: Discussionmentioning
confidence: 99%
“…Micronucleus formation was caused by chromosome lag that prevented chromosomes from entering newly formed cells [27] . The formation of lagging chromosomes is a product of several pre-anaphasic chromosomal irregularities [28] .…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted September 22, 2022. ; https://doi.org/10.1101/2022.09.21.508771 doi: bioRxiv preprint species in which creating mapping populations is challenging and in inter-specific hybrids, where mature COs may lead to chromosome instabilities, preventing conventional mapping (Li et al, 2021;Morales and Dujon, 2012).…”
Section: Discusion High-resolution Mapping Of Cos and Co Intermediate...mentioning
confidence: 99%
“…Using this approach, we found that a large proportion of COs in maize are formed in SNP desert regions, where conventional methods are unable to determine precise CO locations. MLH3 ChIP should also be useful for genetic mapping in species in which creating mapping populations is challenging and in inter-specific hybrids, where mature COs may lead to chromosome instabilities, preventing conventional mapping (Li et al, 2021; Morales and Dujon, 2012).…”
Section: Discusionmentioning
confidence: 99%
“… Zhao et al (2019) found dramatically biased pairing of homoeologous chromosomes and different univalent and chromosome lagging frequencies between C- and H-subgenomes in interspecific hybrids and allotetraploid Cucumis × hytivus through oligo-painting and genomic in situ hybridization (GISH), concluding that the meiotic behavior harmony of subgenomes is important for meiotic evolution. In Saccharum officinarum × Erianthus arundinaceus hybrids, unequal chromosome segregation and chromosome losing were observed during meiosis based on 5S rDNA and 45S rDNA FISH analyses ( Li et al, 2021 ). Definitely, the FISH analysis has developed into a reliable tool for tracing the chromosome behavior during meiosis of plants.…”
Section: Introductionmentioning
confidence: 99%